Influence of juvenile stunting on grow‐out performance of rohu, Labeo rohita (Hamilton, 1822). (13th July 2016) - Das, P. C.; Mishra, S. S.; Mishra, B.; Jayasankar, P.
Summary: Rohu Labeo rohita juveniles stunted for 2, 4, 6, 8 10 and 12 months at 20 and 40 m −3 densities were subsequently cultured for 1 year in six grow‐out earthen ponds each 0.09 ha. Each pond was stocked with juveniles stunted for a particular duration (treatment) at a combined density of 8, 000 ha −1 from two density groups at a 1:1 ratio. Electronic tags were implanted in 20 juveniles of each density group in all treatments as sub‐samples to track fish growth per individual. Another grow‐out study evaluated the growth of a fresh batch of rohu juveniles against similar sized but stunted 12‐month‐old juveniles, stocked together at 8, 000 ha −1 density (1:1). Thirty juveniles from each group in this pond were tagged. After the year‐long grow‐out phase, survival (85.6%–96.3%) showed a positive correlation with the juvenile stunting duration. The study revealed a minimal influence of stunting density on juvenile growth in a subsequent grow‐out phase when they were stunted up to 8 months. But a higher stunting density (40 m −3 ) favoured growth in juveniles stunted for longer periods (>8 months). Growth curves of the lower and higher stunting density groups as well as "all rohu populations" in the treatments showed convergence with those of control (2 months stunted) only in the 4‐month stunted juveniles. The growth convergence in this treatment was achieved within 6 months of culture and subsequently surpassed that of control to over‐compensate at the end of 12 months of culture. No such compensatory growth (CG) response was observed in the 6‐ to 12‐month stunted rohu, because the growth curves run almost parallel to each other. The study also revealed juvenile stunting for more than 6 months delayed the initiation of the growth recovery process in the stunted individuals during their subsequent grow‐out phase. In the second study, identical growth trajectories of the fresh batch and the year‐long stunted juveniles reaffirmed a non‐existence of CG activity in the later. Such results indicate that juvenile stunting in rohu for 6 months and beyond does not lead to a better fish yield or economic gain to farmers, but rather adds to the investment costs because of the need for more feed and maintenance during stunting.